2020
DOI: 10.3390/ijms21041292
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Transcriptomic Analysis of Auxin Responses in Submerged Rice Coleoptile Growth

Abstract: Cultivating rice in wet or water direct seeding systems is simple and time and labor efficient. Rice (Oryza sativa) seeds are a unique cereal that can germinate not only when submerged, but also in anoxic conditions. Many complicated hormone signals interact in submerged seed germination. Ethylene is involved in rice coleoptile elongation, but little is known regarding the role of auxin signaling under submergence. This study demonstrated that the coleoptile is shorter and curlier when submerged with 2,3,5-tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…OsARF , a rice homolog of the ARF, was found to be positively correlated with auxin-dependent differential growth in rice coleoptiles ( Waller et al, 2002 ). Recently, Wu and Yang (2020) have revealed the involvement of auxin signaling in regulating rice coleoptile elongation as well as regulation of carbohydrate metabolism and secondary metabolism under submergence. Besides, auxin plays a key role in cell division during coleoptile elongation in the japonica rice under submergence ( Nghi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…OsARF , a rice homolog of the ARF, was found to be positively correlated with auxin-dependent differential growth in rice coleoptiles ( Waller et al, 2002 ). Recently, Wu and Yang (2020) have revealed the involvement of auxin signaling in regulating rice coleoptile elongation as well as regulation of carbohydrate metabolism and secondary metabolism under submergence. Besides, auxin plays a key role in cell division during coleoptile elongation in the japonica rice under submergence ( Nghi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…ARF7 and ARF19 TFs are known to regulate the expression of LBD16 and LBD29 for lateral organ development in Arabidopsis ( Okushima et al, 2007 ). Recently, it has been shown that these TF genes could be regulated by auxin signaling under submergence ( Wu and Yang, 2020 ), although the function is not known yet. This element could be present in the upregulated genes of all groups for lateral organ development later once the coleoptile reaches the surface of water for O 2 availability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations